Current Ovulation and Luteal Phase Tracking Methods and Technologies for Fertility and Family Planning: A Review - Wegrzynowicz, Andrea K.; Eyvazzadeh, Aimee; Beckley, Amy (Seminars in Reproductive Medicine, 2024)
Ovulation is critical for both conception and overall health, but many people who may ovulate are not tracking ovulation or any other part of their menstrual cycle. Failure to track ovulation, especially in those trying to conceive, can lead to fertility challenges due to absent ovulation, mistiming intercourse, or an undetected luteal phase defect. Ovulatory disorders and mistiming intercourse are both primary causes of infertility, and tracking ovulation is shown to decrease the average time to conception. While there are many tracking methods and apps available, the majority are predictive apps or ovulation predictor kits and do not test or track both successful ovulation and the health of the luteal phase, leading to missing information that could contribute to diagnosis or successful conception. Here, we review why ovulation tracking and a healthy luteal phase are important for those trying to conceive. We present currently available ovulation tracking methods that detect both ovulation and the luteal phase, including cervical mucus, urinary hormone testing, and basal body temperature, and discuss the use, advantages, and disadvantages of each. Finally, we consider the role of digital applications and tracking technologies in ovulation tracking.
Keywords: ovulation tracking; ovulatory dysfunction; infertility; menstrual cycle